Evaluation of Triple helix-forming Oligonucleotides as modulators of transcriptional initiation in erbB-2/HER-2-positive breast cancer : an anti-tumour approach - Dolan, Colette (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2001)
Research over the last several decades has made tremendous strides in the identification of the components of the human genome. Genetic information is expressed by translation of DNA into functional proteins through the intermediate RNA. This has resulted in the development of new concepts in the pathogenesis of disease states. Disease processes have been elucidated as possessing an inherited or acquired genetic basis
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin